Abnormal expression of bHLH3 disrupts a flavonoid homeostasis network, causing differences in pigment composition among mulberry fruits. (1st June 2020) - Li, Han; Yang, Zhen; Zeng, Qiwei; Wang, Shibo; Luo, Yiwei; Huang, Yan; Xin, Youchao; He, Ningjia
Abstract: Mulberry fruits with high concentrations of anthocyanins are favored by consumers because of their good taste, bright color, and high nutritional value. However, neither the regulatory mechanism controlling flavonoid biosynthesis in mulberry nor the molecular basis of different mulberry fruit colors is fully understood. Here, we report that a flavonoid homeostasis network comprising activation and feedback regulation mechanisms determines mulberry fruit color. In vitro and in vivo assays showed that MYBA-bHLH3-TTG1 regulates the biosynthesis of anthocyanins, while TT2L1 and TT2L2 work with bHLH3 or GL3 and form a MYB-bHLH-WD40 (MBW) complex with TTG1 to regulate proanthocyanidin (PA) synthesis. Functional and expression analyses showed that bHLH3 is a key regulator of the regulatory network controlling mulberry fruit coloration and that MYB4 is activated by MBW complexes and participates in negative feedback control of the regulatory network to balance the accumulation of anthocyanins and proanthocyanidins. Our research demonstrates that the interaction between bHLH3 and MYB4 in the homeostasis regulatory network ensures that the fruits accumulate desirable flavonoids and that this network is stable in pigment-rich mulberry fruits. However, the abnormal expression of bHLH3 disrupts the balance of the network and redirects flavonoid metabolic flux in pale-colored fruits, resulting in differences in the levels and proportions of anthocyanins, flavones, and flavonols among differently colored mulberry fruits (red, yellow, and white). The results of our study reveal the molecular basis of the diversity of mulberry fruit colors.